A Good Idea Gone Bad, or Just a Bad Idea? - the Establishment of the Solicitors’ Fidelity Guarantee Fund - Lunney, M (Victoria University of Wellington Law Review, 1997)
This article examines the historical development of the Solicitors’ Fidelity Guarantee Fund in New Zealand. It traces the series of defalcations from solicitors’ trust accounts that occurred during the 1920s and how these events led to some District Law Societies proposing the establishment of a compensation fund. The article also examines the conflicts that occurred between District Law Societies in deciding whether to support the proposal. The author concludes that these historical origins must be considered before any decision regarding abolition of the fidelity fund is made.